2019
DOI: 10.4315/0362-028x.jfp-18-503
|View full text |Cite
|
Sign up to set email alerts
|

Chlorfenapyr Residue in Sweet Persimmon from Farm to Table

Abstract: The use of the pesticide chlorfenapyr has been increasing over time, with a consequent wider application to crops. However, there is limited information available on the amount and safety of the residues it leaves on crops. The amount of chlorfenapyr residues in sweet persimmon (Diospyros kaki L.) at both the pre- and postharvest stages were investigated in this study by calculating its biological half-life. The half-life at the preharvest stage was 8.8 days, shorter than that found during the storage periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…As a registered pesticide directly acting on the pests of cruciferous vegetables, chlorfenapyr has a good control effect, a long-lasting period and is not easy to degrade. At present, the residue detection of chlorfenapyr in tea [ 18 ], chieh-qua [ 19 ], pumpkin and okra [ 20 ], cabbage [ 21 , 22 , 23 ], eggplant [ 24 ], sweet persimmon [ 25 ] and leek [ 26 ] has been reported. However, there has been no report on the residual digestion dynamics of chlorfenapyr in radish and its dietary risk assessment for the population.…”
Section: Introductionmentioning
confidence: 99%
“…As a registered pesticide directly acting on the pests of cruciferous vegetables, chlorfenapyr has a good control effect, a long-lasting period and is not easy to degrade. At present, the residue detection of chlorfenapyr in tea [ 18 ], chieh-qua [ 19 ], pumpkin and okra [ 20 ], cabbage [ 21 , 22 , 23 ], eggplant [ 24 ], sweet persimmon [ 25 ] and leek [ 26 ] has been reported. However, there has been no report on the residual digestion dynamics of chlorfenapyr in radish and its dietary risk assessment for the population.…”
Section: Introductionmentioning
confidence: 99%
“…Polat et al (2019) found that lemon water washing was more effective than the other methods. For the four mentioned insecticides, previous studies also reported that washing and peeling okra fruit, sweet persimmons, eggplants, and strawberries can efficiently decrease their residue levels [ 15 , 16 , 17 , 18 ]. Conversely, the same residues are concentrated by juicing and cooking [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, the consumption of Chl was increased from 5539 t in 2006 to 15 821 t in 2014. 16 However, Chl can cause health issues. [17][18][19] For example, chronic exposure to Chl can cause oxidative damage, apoptosis, and immune disorders in zebrafish liver.…”
Section: Introductionmentioning
confidence: 99%